A randomized controlled study of conventional TBNA versus EBUS-TBNA for diagnosis of suspected stage I and II sarcoidosis - Li, Kaishu; Jiang, Shujuan (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Objectives: The aim of this study was to compare the diagnostic yield of TBNA and EBUS-TBNA in the patients with suspected stage I and II sarcoidosis in the case of the same number of needle aspiration lymph nodes and the same lymph nodes needle aspiration times. Methods: A total of 62 patients with suspected stage I and II sarcoidosis were randomly divided into TBNA group and EBUS-TBNA group, based on the clinical and radiologic manifestations. Biopsy specimens of each patient in both groups were taken from two lymph nodes with two needle passes per lymph node. The diagnostic yields of subgroup were separately calculated including the 4th and 7th lymph nodes (referred to as group A), in other stations (group B), greater than 15 mm and less than 15 mm in the shortest diameter. Results: The diagnostic yield of TBNA and EBUS-TBNA for sarcoidosis was 64% and 93%, respectively (χ2=7.12, P0.05). The percentages of positive pathological diagnosis greater than 15 mm in the shortest diameter were 78% and 94% (χ2=2.29, P>0.05). Conclusion: The overall diagnostic yield of EBUS-TBNA for stage I and II sarcoidosis was higher than TBNA. However, Conventional TBNA has very high diagnostic yield，similar to EBUS-TBNA, if the lymph nodes located on the 4th and 7th group or the shortest diameter was greater than 15 mm.